Effects of Fishmeal Substitution with Mealworm Meals (Tenebrio molitor and Alphitobius diaperinus) on the Growth, Physiobiochemical Response, Digesta Microbiome, and Immune Genes Expression of Atlantic Salmon (Salmo salar) - H-Michael Habte-Tsion; Matt Hawkyard; Wendy M. Sealey; David Bradshaw; Kala-Mallik Meesala; Deborah A. Bouchard (Aquaculture Nutrition)
A 12-week growth trial was conducted to assess the effects of mealworm meals, as a substitution for fishmeal, on the growth, physiobiochemical responses, digesta microbiome, and immune-related genes expression of Atlantic salmon (Salmo salar). Twenty Atlantic salmon parr (38.5 ± 0.1 g, initial weight) were stocked into each of 16 tanks in a recirculating aquaculture system. A fishmeal-based diet (100% FM) was used as the control treatment and was compared with three test diets where: (1) fishmeal was partially (50%) replaced with defatted mealworm meal, Tenebrio molitor (50% DMM), (2) fishmeal was fully replaced with defatted mealworm meal (100% DMM), and (3) fishmeal was partially replaced with whole lesser mealworm meal, Alphitobius diaperinus (50% WMM). All substitutions were done on a crude protein basis. Each of the four experimental diets was evaluated in quadruplicate tanks as part of randomized design. The results indicated that Atlantic salmon showed high survival (greater or equal to 98.8%), and no significant difference in final growth, feed efficiency, feces stability and condition indices. Hepatosomatic index was lower in fish fed 100% DMM and 50% WMM when compared to fish fed the control diet (100% FM). Whole-body proximate and amino acid compositions were not statistically different between treatments, while essential fatty acids, including linolenic, eicosapentaenoic acid, and homo-a-linolenic, were lower in fish fed 100% DMM. Plasma parameters (total protein, alanine aminotransferase, alkaline phosphatase, and total iron-binding capacity), hepatic peroxide, and antioxidant enzymes were not significantly affected by dietary substitutions, whereas plasma immunoglobulin M showed significantly higher levels in fish fed 50% DMM and 100% DMM when compared to fish fed the control diet (100% FM). The inclusion of mealworm meals significantly impacted the overall microbiome composition but not the richness and evenness of the salmon digesta microbiomes compared to control. The most common genus in all treatments was Pseudomonas, which has been previously shown to have both commensal and pathogenic members. The relative expressions of growth (IGF-I) and protein synthesis (TIPRL) were not significantly different between the treatments, whereas immunoglobulin genes (IgM, IgD, and IgT) were significantly upregulated in fish fed the DMM diets when compared to fish fed the control diet. Overall, this study suggests that the mealworm meals tested could be suitable alternatives to fishmeal in the diet of Atlantic salmon.